2001
DOI: 10.1093/glycob/11.6.81r
|View full text |Cite
|
Sign up to set email alerts
|

Sphingolipid activator proteins: proteins with complex functions in lipid degradation and skin biogenesis

Abstract: Sphingolipid activator proteins (SAPs or saposins) are essential cofactors for the lysosomal degradation of membrane-anchored sphingolipids. Four of the five known proteins of this class, SAPs A--D, derive from a single precursor protein and show high homology, whereas the fifth protein, GM2AP, is larger and displays a different secondary structure. Although the main function of all five proteins is assumed to lie in the activation of lipid degradation, their specificities and modes of action seem to differ co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 103 publications
0
50
0
2
Order By: Relevance
“…Sphingolipids are recognized for their importance in skin biology as both structural and signaling molecules (27)(28)(29)(30). Recently, S1P has been shown to have signaling properties that regulate keratinocyte cell function (31)(32)(33)(34)(35)(36).…”
Section: Sphingosine 1-phosphate (S1p)mentioning
confidence: 99%
“…Sphingolipids are recognized for their importance in skin biology as both structural and signaling molecules (27)(28)(29)(30). Recently, S1P has been shown to have signaling properties that regulate keratinocyte cell function (31)(32)(33)(34)(35)(36).…”
Section: Sphingosine 1-phosphate (S1p)mentioning
confidence: 99%
“…It has been suggested that its association with the cell membrane proceeds through the interaction with membrane gangliosides [118,119]. Prosaposin can also be found in many biological fluids such as seminal plasma, human milk, and cerebrospinal fluid (reviewed in [120]). Prosaposin is abundant in the brain where it is localized exclusively in certain neurons [121].…”
Section: Prosaposin Is a Potential Catalyst Of Ganglioside Shedding Amentioning
confidence: 99%
“…Both prosaposin and shed gangliosides were reported to be present in milk and cerebrospinal fluid [120,149,150]. Gangliosides are being actively shed from the membranes [15], and this process appears to be regulated, indicating that it includes specific protein activity.…”
Section: Prosaposin Is a Potential Catalyst Of Ganglioside Shedding Amentioning
confidence: 99%
“…SAPs include five activator proteins, the G M2 activator protein (G M2 AP), and saposins A, B, C, and D (Schuette et al 2001). SAPs act as biological detergents by facilitating the interaction of glycosphingolipid substrates with their respective enzymes for degradation, since glycosphingolipids are unable to interact directly with hydrolytic enzymes in a hydrosoluble milieu (O'Brien and Figure 4 Lysosomal transport of prosaposin truncation/mutation constructs.…”
Section: Discussionmentioning
confidence: 99%
“…Error bars indicate 6 SE, and double asterisks represent p,0.01, compared with PSAP-WT. Kishimoto 1991;Furst and Sandhoff 1992;Mahuran 1998;Schuette et al 2001). Unlike the G M2 AP, saposins A-D derive from a common precursor protein, prosaposin (Hiraiwa et al 1997).…”
Section: Discussionmentioning
confidence: 99%